Phytic Acid and Mineral Biofortification Strategies - Cominelli, Eleonora; Sparvoli, Francesca; Pilu, Roberto (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Two billion people worldwide, mainly in developing countries, where diets are based on the consumption of staple crops, suffer from mineral deficiencies, particularly for iron and zinc. Mineral biofortification includes different strategies aimed to increase mineral concentration and to improve mineral availability from the diet (mineral bioavailability) in the edible parts of plants, particularly the seeds. Phytic acid is a compound that strongly reduces mineral bioavailability as, being highly negatively charged, it strongly binds cations, acting as a magnet. All the contributions in this book aim to describe new results, review the literature, and comment on some of the economic and sociological aspects concerning mineral biofortification research. A number of contributions are related to the study of mineral transport, seed accumulation, and approaches to increase seed micronutrient concentration. The remaining ones are mainly focused on the study of low phytic acid mutants.